Representasi kepemimpinan transformasional kepala sekolah dalam mengembangkan kualitas sekolah melalui supervisi pendidikan Islam - Muhayar, Asep Roni; Romelah (TAWAZUN: Jurnal Pendidikan Islam, 2025)
This study was motivated by the importance of the role of school principals in improving the quality of education through Islamic education supervision oriented towards pedagogical and spiritual guidance. This study aims to analyze the representation of transformational leadership values of school principals in the implementation of Islamic education supervision at SMK Muhammadiyah 2 Malang. The research used a qualitative approach with data collection methods in the form of in-depth interviews and participant observation. The research informants included the principal, vice principal, two teachers, and one student. The data were analyzed descriptively and analytically to reveal the forms of programs, policies, and leadership processes that were implemented. The results show that the principal's transformational leadership is represented through several main programs, namely the habit of performing the Dhuha prayer and congregational zikir as a means of fostering students' morals and character, the Al-Qur'an tahsin program to improve Al-Qur'an reading skills in accordance with the school's vision and mission, and the coaching and development of teacher competencies to improve the quality of learning. These programs reflect the four dimensions of transformational leadership according to Bernard M. Bass, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This study concludes that transformational leadership based on Islamic education supervision contributes significantly to strengthening the quality of education and shaping Islamic character in schools.  Abstrak Penelitian ini dilatarbelakangi oleh pentingnya peran kepemimpinan kepala sekolah dalam meningkatkan kualitas pendidikan melalui supervisi pendidikan Islam yang berorientasi pada pembinaan pedagogis dan spiritual. Penelitian ini bertujuan untuk menganalisis representasi nilai-nilai kepemimpinan transformasional kepala sekolah dalam pelaksanaan supervisi pendidikan Islam di SMK Muhammadiyah 2 Malang. Penelitian menggunakan pendekatan kualitatif dengan metode pengumpulan data berupa wawancara mendalam dan observasi partisipan. Informan penelitian meliputi kepala sekolah, wakil kepala sekolah, dua orang guru, dan satu peserta didik. Data dianalisis secara deskriptif-analitis untuk mengungkap bentuk program, kebijakan, dan proses kepemimpinan yang diterapkan. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional kepala sekolah direpresentasikan melalui beberapa program utama, yaitu pembiasaan shalat Dhuha dan zikir berjamaah sebagai sarana pembinaan akhlak dan karakter peserta didik, program tahsin Al-Qur’an untuk meningkatkan kemampuan membaca Al-Qur’an sesuai visi dan misi sekolah, serta pembinaan dan pengembangan kompetensi guru guna meningkatkan kualitas pembelajaran. Program-program tersebut mencerminkan empat dimensi kepemimpinan transformasional Bernard M. Bass, yaitu idealized influence, inspirational motivation, intellectual stimulation, dan individualized consideration. Penelitian ini menyimpulkan bahwa kepemimpinan transformasional berbasis supervisi pendidikan Islam berkontribusi signifikan dalam penguatan mutu pendidikan dan pembentukan karakter islami di sekolah.